How do migrants' processes of social embedding unfold over time?. (25th July 2020) - Lubbers, Miranda J.; Molina, José Luis; Mccarty, Christopher
Abstract: In this article we investigate how migrants' processes of social (dis‐) embedding in local and transnational contexts unfold over time and illustrate their driving forces. Drawing on unique longitudinal, mixed‐methods social network data of 77 transnational migrants in Barcelona, Spain, we were able to capture changes in social relationships at a micro‐level. We found that migrant embedding is far from a linear process. In many regards, the observed network dynamics are similar to those the literature observed for non‐migrants; for example, the more substantial changes were typically caused by life events. We also found that migrants' opportunities to form new relationships with natives depended on their positions within their places of residence, which were structured by gender, race and class. These results call into question assumptions of individual agency in integration and assimilation debates. Furthermore, they call for a greater presence of temporality and life course scholarship in research into migrants' networks.